Confirmation of the Random Tiling Hypothesis for a Decagonal Quasicrystal - Engel, Michael; Kiselev, Alexander; Trebin, Hans-Rainer (Physical Review Letters, 2012)
Mechanisms that stabilize quasicrystals are much discussed but not finally resolved. We confirm the random tiling hypothesis and its predictions in a fully atomistic decagonal quasicrystal model by calculating the free energy and the phason elastic constants over a wide range of temperatures. The Frenkel-Ladd method is applied for the phonon part, and an approach of uncorrelated phason flips is applied for the configurational part. When lowering the temperature, a phase transition to an approximant occurs. Close to the transition temperature, one of the phason elastic constants becomes soft. © 2012 American Physical Society.